Stress-strain response of A706 grade 80 reinforcing steel. (1st August 2017) - Overby, David; Kowalsky, Mervyn; Seracino, Rudolf
Highlights: A706 grade 80 use in seismic design is currently restricted. 788 tensile tests of A706-80 rebar were conducted. Values of five major stress-strain parameters were statistically identified. No observable susceptibility to strain aging. Abstract: Before ASTM A706 grade 80 rebar may be specified in the seismic design of structures, its mechanical properties must be well understood and calibrated on a statistical basis. Based on the results of 788 tensile tests of A706 grade 80 rebar encompassing bar sizes No. 4–No. 18 (approx. metric No. 13–No. 57), five major stress-strain parameters are statistically evaluated and used to develop recommendations for an expected monotonic stress-strain curve. An existing material model is shown to accurately capture the shape of the monotonic stress-strain curve. Additional tests are used to evaluate the strain-aging performance of the steel.